Analysis of Visible Light Communication Performance in LOS Propagation Model with PSO-Cosh-Based Filter - Fethiye Merve, Kavak Imak; Fatmanur, Atar; Duygu, Kaya; Turgay, Kaya (World Scientific Publ Co Pte Ltd, 2026)
Due to the increasing data transfer in wireless communication technologies, Visible Light Communication (VLC), one of the branches of wireless communication technology, is also developing within this framework. VLC holds an advantage over other communication branches in terms of energy efficiency, high bandwidth, and reliability. In this context, research on VLC-based Light Fidelity (Li-Fi) technology has gained momentum in recent years. In systems built with this Li-Fi technology, data is transmitted through an LED bulb, which is used for illumination. In this study, to analyze the performance of systems where data transmission is provided by VLC, the capacity to improve the shape of the transmitted signal is investigated using systems designed with different filtering techniques under LOS channel conditions. The main objective of this study is to demonstrate the improving effect of the proposed PSO-Cosh-based model on the shape of the transmitted signal compared with traditional filtering methods. In this way, in addition to IIR digital filtering techniques, the analysis of the filter coefficients obtained by optimizing the Cosh window function with Particle Swarm Optimization (PSO) demonstrates the originality of the study.
Keywords: Visible light communication; filters; LED; Li-Fi technology; PSO